POWER, METALLURGICAL AND CHEMICAL MECHANICAL ENGINEERING DEVICE OF PIECEWISE-LINEAR APPROXIMATION OF TRANSIENT RESPONSE OF CONTROLLED ELECTRONIC COMPONENTS - T. A. Ismailov; Kh. M. Gajiyev; D. A. Chelushkin (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objective. The development of a device for the piecewise-linear approximation of a transient response for controlling an automated system of the production diagnosis of electronic component parameters on functional cells.Methods. A new measuring input circuit was developed for the control of defective electronic components on functional cells in order to obtain the integral transient response, provided that circuit parameters can be programmatically altered. In this case, there is no need to exclude the shunting influence of neighbouring elements on functional cells, since all parameters of all electronic equipment connected to the controlled points are taken into account and will influence the formation of the transient process.Results. The input measuring integrated circuit is capable of controlling the transient responses of both individual electronic components and their groups, consisting of various types of active and passive electronic components. The dependency between the systematic error in the piecewise-linear approximation of the transient response of the electronic components on functional cells and the time constant (T) of the input circuit of the measurement unit is established. The minimum value of the systematic error will be obtained with a time constant of the input circuit equal to 0.001 sec.Conclusion. The information form converter in the automated production diagnostic system for monitoring transient response from the diagnosed electronic components after the stimulating voltage drop has been applied will significantly reduce the time for monitoring each functional cell due to a faster conversion process and a simpler process for comparison with reference.